Mesoscale avalanche size underpins the rheology of granular yielding - Keng-Lin Lee; Ting-Yin Yeh (Proceedings of the National Academy of Sciences, 2025)
Granular materials under loading exhibit intermittent avalanches of varying sizes prior to full yielding, a hallmark of natural failure phenomena such as landslides and earthquakes. While continuum models for postyield plastic flow are well established, a unified framework connecting preyield avalanche dynamics to bulk rheology remains lacking. Here, we introduce a birefringent double-shear experiment that enables sustained probing of avalanche statistics and quasistatic flow behavior near the yielding transition. We find that the avalanche regime exhibits rate-weakening behavior, while the plastic regime is rate-independent, resulting in dual rheology under identical local shear rates and indicating hysteresis and mechanical instability. Within a stress-activated framework, we identify the mean normalized stress drop, a measure for mesoscale avalanche size, as a key field variable that bridges the two regimes. Incorporating this variable, we formulate a unified constitutive model that captures the entire yielding transition. These findings establish mesoscale avalanche evolution as a central mechanism underlying granular yielding rheology.